FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KEKURANGAN ENERGI KRONIK (KEK) PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS MACCINI SOMBALA MAKASSAR - Rosdiana Syakur; Musaidah Musaidah; Jusman Usman; Nur Ismala Dewi (Jurnal Komunitas Kesehatan Masyarakat, 2020)
The deficiency of the cronic energy is a condition where a person's nutritional status is in a bad condition. This can be caused by lack of food consumption and energy sources that contain micro-substances. The needs of pregnant women will increase than usual where the exchange of almost all the burden occurrence is very active, especially in the third trimester.The research aimed at determining the relationship between the age of pregnant women, the education of pregnant women, the parity of pregnant women, the knowledge of pregnant women, the frequency of eating and the incidence of the chronic energy deficiency in pregnant women. The research used is observational method with a cross sectional study approach. Sampling was carried out by using purposive sampling technique with a sample of 68 pregnant women. Data were analyzed by using the chi-square test. The result of research indicates that the age of pregnant women is related to the chronic energy deficiency with a value of p (0,000) <0.05, the education of pregnant women is related to the chronic energy deficiency with a value of p (0,000) <0.05, the parity is associated with the chronic energy deficiency with p value (0.001) <0.05, the knowledge is related to chronic energy deficiency with p value (0,000) <0.05, the eating frequency is related to chronic energy deficiency with p value (0,000) <0.05. The research concludes that the age of pregnant women,the education of pregnant women, the parity, the knowledge, the frequency of eating are related to the incidence of the chronic energy deficiency. The results of this research are expected to be useful for pregnant women, researchers and for the public health centers so that they can improve and provide counseling to pregnant women, to pay more attention to the health and consumption of nutritious foods during pregnancy.